A cross-sectional survey of bacterial species in plaque from client owned dogs with healthy gingiva, gingivitis or mild periodontitis. - Ian J Davis; Corrin Wallis; Oliver Deusch; Alison Colyer; Lisa Milella; Nick Loman; Stephen Harris; Stephen Harris (PLoS ONE)
Periodontal disease is the most widespread oral disease in dogs which if left untreated results in significant pain to the pet and loss of dentition. The objective of this study was to identify bacterial species in canine plaque that are significantly associated with health, gingivitis and mild periodontitis (<25% attachment loss). In this survey subgingival plaque samples were collected from 223 dogs with healthy gingiva, gingivitis and mild periodontitis with 72 to 77 samples per health status. DNA was extracted from the plaque samples and subjected to PCR amplification of the V1-V3 region of the 16S rDNA. Pyrosequencing of the PCR amplicons identified a total of 274 operational taxonomic units after bioinformatic and statistical analysis. Porphyromonas was the most abundant genus in all disease stages, particularly in health along with Moraxella and Bergeyella. Peptostreptococcus, Actinomyces, and Peptostreptococcaceae were the most abundant genera in mild periodontitis. Logistic regression analysis identified species from each of these genera that were significantly associated with health, gingivitis or mild periodontitis. Principal component analysis showed distinct community profiles in health and disease. The species identified show some similarities with health and periodontal disease in humans but also major differences. In contrast to human, healthy canine plaque was found to be dominated by Gram negative bacterial species whereas Gram positive anaerobic species predominate in disease. The scale of this study surpasses previously published research and enhances our understanding of the bacterial species present in canine subgingival plaque and their associations with health and early periodontal disease.